2020
DOI: 10.1002/ss.20366
|View full text |Cite
|
Sign up to set email alerts
|

Translating rural Latinx students’ cultural wealth to college campuses

Abstract: Asset‐based thinking and practice is a necessary approach to meeting the needs of rural Latinx students. This chapter provides an overview of asset‐based narratives among Latinx and rural Latinx students while offering recommendations for educators to enhance their capacity to facilitate the success of this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Limited access to nearby and quality higher education institutions has been found to negatively impact rural student college access and enrollment, as proximity to colleges significantly affects the likelihood of college application, especially at four-year colleges [6]. While these studies highlight some challenges rural students face when accessing higher education, research has also found that they have high college aspirations [7] and cultural wealth [8][9][10] that higher education institutions can nurture to ensure their collegiate success.…”
Section: Introductionmentioning
confidence: 99%
“…Limited access to nearby and quality higher education institutions has been found to negatively impact rural student college access and enrollment, as proximity to colleges significantly affects the likelihood of college application, especially at four-year colleges [6]. While these studies highlight some challenges rural students face when accessing higher education, research has also found that they have high college aspirations [7] and cultural wealth [8][9][10] that higher education institutions can nurture to ensure their collegiate success.…”
Section: Introductionmentioning
confidence: 99%
“…Rurality is often portrayed in a monolithic light, but this does not mean that rural people are identical (Means, 2019;Cain & Willis, 2022;McNamee, 2019). For instance, research on Black and Latinx rural youth highlights the intersectionality of race and rural identity and encourages educators and policymakers to consider these dynamics as a way to advance equity (Hallmark et al, 2023;Marlow-McCowin et al, 2020;Means, 2019). Similarly, the research of Cain and Class (2023), Kryst et al (2018), andLi (2019) bring to attention the wide spectrum of socioeconomic status and family wealth in research on rural students.…”
Section: Rural Mindsets and Valuesmentioning
confidence: 99%
“…Several scholars have noted that intentional collaboration between high schools and colleges has yielded successful results for college access (Harmon, 2017;Ohlson et al, 2020, Marlow-McCowin et al, 2020. For instance, when colleges share some of their resources with high schools (e.g., guest faculty presentations or the use of equipment or space), the high school students both benefit from the resources while also become familiar with the idea of college as an option.…”
Section: Successful Rural College Access and Pre-college Career Devel...mentioning
confidence: 99%
See 2 more Smart Citations